2012
DOI: 10.1080/08927014.2012.689288
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning of surfaces by macromolecules and its implication for the settlement of zoospores of the green algaUlva linza

Abstract: Conditioning, ie the adsorption of proteins and other macromolecules, is the first process that occurs in the natural environment once a surface is immersed in seawater, but no information is available either regarding the conditioning of surfaces by artificial seawater or whether conditioning affects data obtained from laboratory assays. A range of self-assembled monolayers (SAMs) with different chemical terminations was used to investigate the time-dependent formation of conditioning layers in commercial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 32 publications
6
74
0
Order By: Relevance
“…Especially ethylene glycol (EG) x -containing coatings have been used in the biomedical area [21][22][23][24] and have recently been investigated with respect to their marine anti-fouling potential [25][26][27][28][29][30][31][32][33]. However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35]. Other promising approaches involve the use of amphiphilic [26,27,29,36] or zwitterionic chemistries [37][38][39][40].…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
See 2 more Smart Citations
“…Especially ethylene glycol (EG) x -containing coatings have been used in the biomedical area [21][22][23][24] and have recently been investigated with respect to their marine anti-fouling potential [25][26][27][28][29][30][31][32][33]. However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35]. Other promising approaches involve the use of amphiphilic [26,27,29,36] or zwitterionic chemistries [37][38][39][40].…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…FOTS) as the probability to observe patterns indicative of an attractive surface vanish over time [61]. On such hydrophobic surfaces, conditioning films are formed within hours and Thomé et al [35] revealed that the presence of such overlayers decreases the settlement rates of Ulva zoospores by &50 %. Thus it is likely that surface conditioning affects the deceleration and the probability to observe certain motion patterns.…”
Section: The Spinning Motion Tests the Strength Of Temporary Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,[47][48] Understanding how organic material such as proteins interact and adsorb onto surfaces is important in itself, in order to study correlations with the settlement and adhesion of marine fouling organisms, which frequently use proteinaceous adhesives, or for understanding how macromolecules act to induce gregarious settlement or metamorphosis. 49 Surface resistance to nonspecific protein adsorption is also essential for development of biomaterials and biomedical devices.…”
Section: Biofouling Assaysmentioning
confidence: 99%
“…Then, dishes were placed on a rotary shaker at room temperature and shaken for 1 h at 50 rpm to allow attachment of bacteria to the test surfaces. After removing the bacterial suspension, the slides were washed with 10 mL of ASW on a rotary shaker for (1997) 43 and Thome et al (2012). 44 Three replicates of each test surface were placed separately in polystyrene Quadriperm dishes (Greiner Bio-One Ltd.) and 10 mL of spores suspension with OD600nm = 0.15 (1.0 x 10 6 spores ml -1 ) were added.…”
mentioning
confidence: 99%